2021
DOI: 10.1108/jocm-11-2020-0364
|View full text |Cite
|
Sign up to set email alerts
|

Empowering leadership and knowledge management: the mediating role of followers' technology use

Abstract: PurposeThe purpose of this paper is to investigate the role of empowering leadership in intraorganizational knowledge management practices and to reveal how followers' acceptance and use of the hotel management system affect this role.Design/methodology/approachA serial multiple mediation model was evaluated and tested using partial least squares structural equation modeling (PLS-SEM). The database was created from the results of a structured questionnaire obtained from 401 employees working in hotels in Turke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 82 publications
1
9
0
1
Order By: Relevance
“…, 2021; Jiang et al. , 2021), innovative behavior (Mutonyi et al , 2020), knowledge sharing behavior (Türkmendağ and Tuna, 2021) and task performance (Byun et al , 2020). A few studies have examined the effect of empowering leadership on employees' work engagement (Lee et al.…”
Section: Introductionmentioning
confidence: 99%
“…, 2021; Jiang et al. , 2021), innovative behavior (Mutonyi et al , 2020), knowledge sharing behavior (Türkmendağ and Tuna, 2021) and task performance (Byun et al , 2020). A few studies have examined the effect of empowering leadership on employees' work engagement (Lee et al.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, our findings provide three types of strategic activities meant to encourage employees' empowerment: (1) federate team spirit to facilitate collaboration; (2) develop employees' capabilities and (3) adjust managers' activities according to employees' needs. These results go beyond the banking sector and provide an empirical illustration of the progressive development of empowering leadership micro-practices (Cheong et al ., 2016; Li et al ., 2016; Türkmendağ and Tuna, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Chen and Aklikokou (2020) highlighted that perceived usefulness and perceived ease of use act in a mediating role among social influence, trustworthiness, facilitation conditions, and behavioral intention to use e-government services. Likewise, Türkmendağ and Tuna (2022) demonstrated that the acceptance and use of a hotel management system mediated the influence of leadership empowerment on knowledge management practices.…”
Section: The Mediating Role Of System Use (Su)mentioning
confidence: 99%